2011
DOI: 10.1172/jci45843
|View full text |Cite
|
Sign up to set email alerts
|

3BP2-deficient mice are osteoporotic with impaired osteoblast and osteoclast functions

Abstract: A fine balance between bone resorption by osteoclasts and bone formation by osteoblasts maintains bone homeostasis. In patients with cherubism, gain-of-function mutations in 3BP2, which is encoded by SH3-domain binding protein 2 (SH3BP2), cause cystic lesions with activated osteoclasts that lead to craniofacial abnormalities. However, little is known about the function of wild-type 3BP2 in regulating bone homeostasis. Here we have shown that 3BP2 is required for the normal function of both osteoblasts and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 63 publications
6
65
1
Order By: Relevance
“…This is a previously unrecognized link between MITF and 3BP2 expression and further studies are needed to dissect the mechanism. MITF is essential for osteoclast development and function (52) and 3BP2 is essential for coordinating bone homeostatic signals in both osteoclast and osteoblast lineages (53). In the bone metabolism context 3BP2 has been shown to regulate the bone marrow monocyte response to macrophage and osteoclast differentiation signals downstream of the receptors for macrophage colony-stimulating factor (M-CSF) and the receptor activator of nuclear factor kappaB ligand (RANKL) through mechanisms that involve control of extracellular signal-regulated kinase (ERK) and spleen tyrosine kinase (SYK) activity, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…This is a previously unrecognized link between MITF and 3BP2 expression and further studies are needed to dissect the mechanism. MITF is essential for osteoclast development and function (52) and 3BP2 is essential for coordinating bone homeostatic signals in both osteoclast and osteoblast lineages (53). In the bone metabolism context 3BP2 has been shown to regulate the bone marrow monocyte response to macrophage and osteoclast differentiation signals downstream of the receptors for macrophage colony-stimulating factor (M-CSF) and the receptor activator of nuclear factor kappaB ligand (RANKL) through mechanisms that involve control of extracellular signal-regulated kinase (ERK) and spleen tyrosine kinase (SYK) activity, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…The number (N) of nuclei per osteoclast in TRAP stained sections of the secondary spongiosa of proximal tibia in WT and Cldn-18 −/− mice at 4 weeks of age was determined as previously described (37). Briefly, twenty osteoclasts per sample were randomly selected with operator blinded, before osteoclasts were sorted based on 1–2 and 3–6 N.Nuclei per osteoclast.…”
Section: Methodsmentioning
confidence: 99%
“…Heterozygous mutations in the signaling adaptor protein SH3-domain binding protein 2 (SH3BP2) are responsible for the disorder (Ueki et al, 2001). SH3BP2, originally discovered as a protein that binds to ABL (Ren et al, 1993), has been found to interact with a variety of proteins including SYK (Deckert et al, 1998), VAV (Foucault et al, 2005), PLCγ1 and PLCγ2 (Deckert et al, 1998; Jevremovic et al, 2001), and SRC (Levaot et al, 2011a) in various cells. Phosphorylation of tyrosine residues in SH3BP2 by SYK modulates downstream signaling pathways (Maeno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%